The influence of measurement density on micro-instability testing - Daling, Nika (Student Undergraduate Research E-journal!, 2016)
Protection from water flooding by dikes is an important issue in the Netherlands. Therefore dikes have to be regularly tested for possible failure, for example caused by micro-instability. Micro-instability occurs in the upper layer of the dike, due to water flowing through it. The goal of this research was to determine the influence of the measurement density on safety assessment of river dikes for micro-instability and in addition to give a confidence interval for these assessments. This paper shows that uncertainty in cover layer thickness has the largest effect on the reliability of dike safety assessment in relation to micro-instability.